Rehabilitation as one of the guarantees of the rights to protect the suspect, the accused in the criminal process (Journal of actual problems of jurisprudence, 2018)
The article is devoted to rehabilitation as one of the guarantees of the rights to protect a suspect who is accused in a criminal process. Rehabilitation in criminal proceedings should be understood as the official recognition of a citizen’s innocence of a criminal offense, expressed in the relevant legal act, entailing compensation for the harm caused, as well as restoration of other rights violated as a result of illegal or unjustified criminal prosecution and / or conviction. Rehabilitation law has a criminal procedural nature, since it originates from the criminal process –official suspicion or accusation of a criminal offense.The main purpose of this article is to consider compensation for property damage, compensationfor non-pecuniary damage, restoration of other rights are derivative tasks, the main one is to correct aninvestigative, judicial error, and this is the prerogative of the criminal process.This article, in particular, states that the harm that was caused to a person and a citizen as a resultof unlawful criminal prosecution should be reimbursed by the state in full, regardless of the fault of thebodies that conducted the inquiry or the inquiry officer, prosecutor, investigator and court.In order to create the right to rehabilitation, it is necessary and sufficient only to admit that the unlawfulcriminal prosecution was conducted with violations of the procedure for conducting criminal proceedings.That is, due to unlawful actions or omissions carried out by state authorities or their officials,and these actions or inaction could lead to an unlawful commencement of a pre-trial investigation of acriminal case, unlawful detention or an unlawful criminal charge.Key words: rehabilitation, suspect, accused, property damage, moral damage, criminal prosecution,legal proceedings.